Partial double-pruning after bloom delays bunch rot epidemics in Vitis vinifera L. cvs. Riesling and Pinot gris - Daniel Molitor; Mareike Schultz; Doriane Dam; Marine Pallez-Barthel; Matthias Friedel; Marco Beyer (OENO One, 2022)
Bunch rot caused by Botrytis cinerea is a major fungal disease in grapevines. Under humid climatic conditions, bunch rot development on grapes cannot be completely suppressed and bunch rot control strategies mainly aim to delay the epidemic. In the present study, we investigated the potential of the innovative cultural practice “partial double-pruning after bloom (PDP)” to delay the bunch rot epidemic on Pinot gris and Riesling cultivars over five consecutive seasons (2016-2020) in Remich/Luxembourg. Control vines were pruned at winter to one 10-node fruiting cane per vine, while in PDP, two 10-node fruiting canes per vine were kept; one of the two canes was removed at BBCH 73 (2-3 weeks after bloom). In all the 10 cultivar*year combinations, the bunch rot disease severity at the final assessment date (shortly before harvest) was lower in PDP than in the control. This reduction was significant (P £ 0.05) in 7 of the 10 cultivar*year combinations. PDP significantly delayed the date when 5 % disease severity was reached; in data pooled over the five years this delay ranged between 10.3 (Pinot gris) and 8.3 days (Riesling). The proportion of non-marketable fruit was significantly reduced by 41 % (Pinot gris) and 53 % (Riesling). Total yield per plant was reduced by 10 % (Pinot gris) and 19 % (Riesling), with a significant increase in total soluble solids at harvest in the case of Riesling. An additional evaluation in the year 2020 revealed reduced cluster compactness in PDP for both cultivars. PDP turned out to be an innovative, efficient, reliable and relatively cost-efficient cultural practice to delay the bunch rot epidemic in grapes. It can be integrated as one module into the best practice strategy to control bunch rot and contributes to pesticide reduction in viticulture.